Haematopoietic stem cell transplantation for treatment of primary CNS lymphoma: single‐centre experience and literature review. (23rd March 2015) - Bojic, Marija; Berghoff, Anna S.; Troch, Marlene; Agis, Hermine; Sperr, Wolfgang R.; Widhalm, Georg; Wöhrer, Adelheid; Kalhs, Peter; Preusser, Matthias; Rabitsch, Werner
Abstract Primary central nervous system lymphoma (PCNSL) is a rare and malignant tumour type. Established treatment approaches include high‐dose methotrexate (HD‐MTX)‐based chemotherapy and whole‐brain radiotherapy (WBRT). WBRT is associated with significant neurotoxicity and autologous haematopoietic stem cell transplantation (ASCT) has been proposed as an alternative treatment – either in the 1st line setting after HD‐MTX‐based chemotherapy or as salvage treatment for relapsed/refractory PCNSL. We here report our single‐centre experience with five PCNSL patients, who had achieved an objective response after a high‐dose methotrexate‐based induction therapy and consecutively received a high‐dose chemotherapy, consisting of carmustine and thiotepa, followed by ASCT. We also provide a literature review on ASCL for PCNSL. Our data, with three of five patients in continuous complete remission and four of five patients alive after a median follow‐up time of 8 months, as well as previously published results, show that ASCT is a safe treatment option that is able to induce tumour remissions in patients with PCNSL. However, controlled trials are needed to compare the long‐term efficacy and tolerability of ASCT with other treatment approaches and also to establish the optimal sequence of treatment regimens in PCNSL patients.